Program OSDI: Omah Sampah Digital Berbasis Zero Waste Community di Desa Ngablak - Rahayu, Artika Dwi; Hidayat, Taufiq (IKIP PGRI Bojonegoro, 2024)
ABSTRACTThe establishment of a waste bank will not fully change for many people without the awareness of the importance of waste management. The lack of knowledge about household waste management is the reason for this community service program. This program aims to raise awareness and improve community skills in Ngablak Village, Dander District, Bojonegoro Regency through the Program OSDI: Omah Sampah Digital. Through this program, it is expected that the community will independently manage their household waste and strengthen the waste bank management by utilizing digital technology. This program covers waste management training, community building, and development of digital platforms for waste bank management, namely “OSDI” and “Omah Sampah Digital”. The community service program is carried out by conducting awareness activities, developing a zero waste community, providing training on waste management and digital waste bank management. This community service program has received positive feedback from the community, and it is expected to contribute to environmental sustainability.ABSTRAKPembangunan bank sampah tidak akan merubah sepenuhnya kebiasaan masyarakat apabila tidak diimbangi dengan kesadaran akan pentingnya pengelolaan sampah. Kurangnya pengetahuan pengelolaan limbah rumah tangga menjadi latar belakangan kegiatan pengabdian masyarakat ini. Program pengabdian masyarakat ini bertujuan untuk meningkatkan kesadaran dan keterampilan masyarakat Desa Ngablak, Kecamatan Dander, Kabupaten Bojonegoro melalui Program OSDI: Omah Sampah Digital. Melalui program ini, diharapkan masyarakat dapat mengelola limbah rumah tangga secara mandiri, serta memperkuat pengelolaan bank sampah dengan memanfaatkan teknologi digital. Program ini mencakup pelatihan pengelolaan limbah, pembentukan komunitas dan pembuatan aplikasi manajemen bank sampah yaitu “OSDI” dan “Omah Sampah Digital”. Metode kegiatan pengabdian ini dilakukan dengan memberikan sosialisasi, membentuk komunitas zero waste, memberikan pelatihan pengelolaan sampah dan bank sampah digital. Program pengabdian masyarakat ini telah mendapatkan respon dan hasil positif dari masyarakat serta dapat memberikan manfaat untuk keberkelanjutan lingkungan.